Blended Learning: Workshop Penggunaan Google Form dan Google Classroom Bagi Guru SMP Negeri 34 Semarang - Agnita Siska Pramasdyahsari; Sutrisno Sutrisno; Rina Dwi Setyawati; Noviana Dini Rahmawati; Dhian Endawuri (LPPM Universitas Timor, 2020)
The main problems of SMP Negeri 34 Semarang are (1) do not have human resources who capable of implementing blended learning, especially by using the google form and google classroom; (2) teachers have not used information technology optimally; (3) the teacher is not yet technically optimal in publishing teaching materials and instructional media using technology. Therefore, to improve the teachers’ ability in providing learning media that are more interesting and enjoyable, a blended learning workshop is provided for making google forms and google classroom. The methods in this partnership program are lectures, practices, questions-answers and assignments. The program was occured for two days with details of the first day's workshop on google forms along with their practices and assignments. Meanwhile, the second day's workshop was on google classroom along with practices and assignments. The results of this activity are workshop participants are able to create an account, design teaching materials and evaluation tools through google forms and google classroom. In addition, teachers are more technically optimal in publishing teaching materials and learning media using technology.